Role of Medicinal Plants in Modern Medicine - A.H1, Gilani, (Malaysian Journal of Science, 2005)
The use of plants, plant extracts or pure chemicals isolated form natural products to treat disease is a therapeutic modality, which has stood the test of time even if much of the science behind such therapy is still in its infancy. Indeed today many pharmacological classes of drugs include a natural product prototype. Morphine, digoxin, quinine, atropine, reserpine, physostigmine, pilocarpine, vincristine, vinblastine, artimesinin and taxol are a few examples of what medicinal plants have given us in the past. Some active principles have limited application in modem medicine but are invaluable as pharmacological "tools" for evaluating the mode of action of other drugs or investigation of basic physiological function. Some examples are atropine, muscarine, nicotine, cocaine, reserpine, yohimbine and himbacine. The modem medicine is now beginning to accept the use of botanicals once they are scientifically validated. Ispaghula, Garlic, Ginkgo, St. John's Wort, Saw palmetto are a few examples of botanicals which are gaining popularity amongst modem physicians. The number of plants that still have not been studied for content of biologically active compounds is vast. Only 3-5% of terrestrial plants have been reasonably well investigated and hence there is huge potential on research on medicinal plants. Teamwork amongst ethnobotanists, Ethnopharmacologists and Phytochemists is essential for the fruitful outcome on medicinal plants research.